Lumped Elements for RF and Microwave Circuits, Second Edition - Bahl, Inder (Artech, 2022)
Fully updated and including entirely new chapters, this Second Edition provides in-depth coverage of the different types of RF and microwave circuit elements, including inductors, capacitors, resistors, transformers, via holes, airbridges, and crossovers. Featuring extensive formulas for lumped elements, design trade-offs, and an updated and current list of references, the book helps you understand the value and usefulness of lumped elements in the design of RF, microwave and millimeter wave components and circuits. You’ll find a balanced treatment between standalone lumped elements and their circuits using MICs, MMICs and RFICs technologies. You’ll also find detailed information on a broader range RFICs that was not available when the popular first edition was published. The book captures – in one consolidated volume -- the fundamentals, equations, modeling, examples, references and overall procedures to design, test and produce microwave components that are indispensable in industry and academia today. With its superb organization and expanded coverage of the subject, this is a must-have, go-to resource for practicing engineers and researchers in industry, government and university and microwave engineers working in the antenna area. Students will also find it a useful reference with its clear explanations, many examples and practical modeling guidelines.